ANalgesic Efficacy and safety of MOrphiNe versus methoxyflurane in patients with acute myocardial infarction: the rationale and design of the ANEMON-SIRIO 3 study: a multicentre, open-label, phase II, randomised clinical trial. Issue 3 (1st March 2021) - Kubica, Aldona; Kosobucka, Agata; Niezgoda, Piotr; Adamski, Piotr; Buszko, Katarzyna; Lesiak, Maciej; Wojakowski, Wojciech; Gasior, Mariusz; Gorący, Jarosław; Kleinrok, Andrzej; Nadolny, Klaudiusz; Navarese, Eliano; et al.
Abstract : Introduction: The unfavourable influence of morphine on the pharmacokinetics of ticagrelor resulting in weaker and retarded antiplatelet effect in patients with acute coronary syndrome (ACS) has been previously shown. Replacing morphine with methoxyflurane, a potent, non-opioid analgesic agent, that does not weaken or delay the effect of antiplatelet agents may improve the clinical efficacy of treatment of patients with ACS. Methods: The ANEMON-SIRIO 3 study was designed as a multicentre, open-label, phase II, randomised clinical trial aimed to test the analgesic efficacy and safety of methoxyflurane in patients with ACS. The study population will comprise patients with ST-elevation myocardial infarction or non-ST-elevation ACS admitted to the study centres with typical chest pain requiring analgesic treatment. Before percutaneous coronary intervention (PCI) for the patients with index ACS will be randomly assigned in 1:1 ratio to receive methoxyflurane administered by inhalation, or to obtain morphine administered intravenously. Analgesic treatment will be followed by 300 mg loading dose of aspirin and 180 mg loading dose of ticagrelor. Patients will be assessed with regard to pain intensity according to the Numeric Pain Rating Scale at baseline, 3 min after study drug administration and immediately after PCI. Moreover, patients will be actively monitored with regard to the occurrence of side effects of evaluated therapies, as well as adverse events that may be related to insufficient platelet inhibition (no-reflow phenomenon assessed immediately after PCI, administration of GPIIb/IIIa inhibitors during PCI, acute stent thrombosis). Ethics and dissemination: The study will be conducted in six Polish clinical centres from the beginning of in accordance with the ethical standards of the institutional research committee and with the 1964 Helsinki declaration and its later amendments or comparable ethical standards. Trial registration details: ClinicalTrials.gov, NCT04476173 .